Qualitative Research on Islamic Psychotherapy: A Metasynthesis Study in Indonesia - Trimulyaningsih, Nita (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
There was no conclusions about the concept of Islamic psychotherapy in Indonesia. This conclusions is important in the building of paradigm of Islamic Psychology that was fit with Indonesian culture. This study tried to synthesis the qualitative research of Islamic Psychotherapy to describe real experience of Islamic psychotherapy in Indonesia. Methods of this research was qualitative metasynthesis. The approach used in this research was reciprocal translation which adapted from metaethnography. From the result, Islamic psychotherapy was defined as Techniques to solve the clients problems and treating illness both mental, spiritual, moral, or physical by increasing the awareness of Allah and getting back the client to Allah, in Islamic approach through guidance of Quran and hadits. Three varians of Islamic psychotherapy in Indonesia was sufism, worship psychotherapy, and religious guidance. Basic assumption about fitrah and tauhid found underlying all of the concept and practice of Islamic psychotherapy in Indonesia.